1985
DOI: 10.1037/0735-7044.99.6.1162
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in food intake and activity in domestic cats.

Abstract: Daily patterns of food intake and activity were determined for normal cats and cats with pontile lesions. Food intake in the dark and in the light of LD (light/dark) cycles were determined separately by weighing the food, and a "percentage nocturnal" score was calculated. The measure of activity was infrared photobeam interruptions, with the photobeam placed in front of the cages, over the food bowl. No differences between normal cats and cats with pontile lesions were detected for any of the measures. Food in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…In laboratory facilities, the importance of interactions between human beings and animals, and the social affinity of domesticated animals for human beings, are often ignored (Benn 1995). Randall and others (1985, 1990) showed that laboratory cats organise their daily activity patterns around the activities of their human caretakers, and respond strongly to people in their environment. Cats kept in enriched conditions in a laboratory facility showed a clear preference for human contact over toys (DeLuca and Kranda 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory facilities, the importance of interactions between human beings and animals, and the social affinity of domesticated animals for human beings, are often ignored (Benn 1995). Randall and others (1985, 1990) showed that laboratory cats organise their daily activity patterns around the activities of their human caretakers, and respond strongly to people in their environment. Cats kept in enriched conditions in a laboratory facility showed a clear preference for human contact over toys (DeLuca and Kranda 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in age between any of the groups ( F  = 0.93, p  = 0.46, one-way ANOVA). Circadian factors are unlikely to play a role in sleep-dependent ocular dominance plasticity because circadian rhythms in sleep/wake and other parameters are extremely weak in cats [66][68] and entirely absent in critical period kittens [69]. Nevertheless, all experimental manipulations were done at the same time of day.…”
Section: Methodsmentioning
confidence: 99%
“…They also demonstrated the existence of a bimodal pattern of wakefulness displaying dawn and dusk peaks under artificial light: dark cycle. Randall et al [25] found a free-running circadian organisation of activity in cats kept in constant darkness as measured by infrared photobeams. These cats, isolated from humans to human noises, showed, in addition, random patterns of activity when kept in constant light.…”
Section: Introductionmentioning
confidence: 99%